BREAK-EVEN ANALYSIS: ITS USES AND MISUSES. - Stettler, Howard F. (The Accounting Review, 1962)
Abstract Break-even analysis is capable of living up to its name and showing the volume level at which expenses and revenues are equal, but if, as contended, this is the only use generally made of such information, the use is not only deficient, but may involve an actual disservice as well. The purpose of this article is to point out the fallacies in the way break-even point information and break-even analysis have sometimes been used and to suggest more significant uses of these tools than as mere means of satisfying idle curiosity. Appropriate uses have been suggested as being primarily in the area of managerial planning and review, including detection of unplanned change, overall review of budget planning, and evaluation of new proposals and alternative actions. of the wealth of material that has appeared in recent years on the technical problems of break-even analysis, no consideration has been given to such matters as changes in product mix, price-level changes, allocation of fixed costs between plants or products, or non-linear cost factors. These factors are, however, of major importance and must be given due consideration in break-even point determinations.